Cultivating Excellence: The Impact of Organizational Culture of BerAKHLAK and Civil Servants’ Competence on Performance - Fitriana, Yuni; Farida, Florentina Anif (Target : Jurnal Manajemen Bisnis, 2024)
effect and are followed by all organization members. The organizational culture of respect is the key to direct management and employees in deciding and establishing policies in government agencies. This research aims to analyze the influence of the organizational culture of respect and competence on the performance of civil servants in the Dinas Pekerjaan Umum dan Penataan Ruang (DPUPR). The method used in this research is a quantitative method with a total sample of 42 civil servants. This research used a saturated sampling technique and used multiple linear regression analysis. The study results show that the organizational culture of respect and civil servants’ competence significantly positively affect employee performance. This research contributes to enhancing the understanding of the DPUPR in Madiun, Indonesia, by examining its current organizational culture. It serves as a benchmark for gauging employees' perceptions in fulfilling their civil service responsibilities, thereby influencing their task performance and competency levels toward achieving excellence in their roles.